(untitled) (Revista de Estudos da Linguagem, 2024)
The aim of this study is to provide updated evidence of the use of non-adapted, adapted and false sports-related anglicisms in the European Spanish press. Specifically, this piece of research attempts to unveil technical/semi-technical English borrowings and to explore the pragmatic functions of these English lexical units in the current digital Spanish newswire. The method consisted of examining eight different media by using the constantly updating database of anglicisms ‘Observatorio Lázaro’ throughout a period of 9 months. A sample of 130 English lexical items was collected and subjected to an in-depth qualitative and descriptive analysis. Each borrowing was looked up in DAD ‒the most recent dictionary of sports-related English lexical items in Spanish‒ and was illustrated by a real example of its use in context excerpted from present-day Spanish newspapers. Terminology associated to a broad spectrum of specific sports –such as golf, basketball, rugby, cycling, etc.– was delved into. Results show that, while some terms have no connection to the rest of borrowings, many of them can be grouped according to certain parameters. Considering pragmatic functions, the use of some anglicisms proved not to be random but to respond to news reporters’ and journalists’ purposes. The study concludes that the pervasive influence exerted by English on Spanish concerning technical/semi-technical sports anglicisms remains in full force and effect nowadays, as this impact affects the vocabulary of a wide variety of sports games and exercises.